An Overview of Good Faith as a Principle of Contractual Interpretation with Special References to the Albanian Law - Gjoni, Gjin; Peto, Zhaklina (European Scientific Journal, ESJ, 2017)
Good faith is one of the most discussed topics in the jurists' circle, seen as a key argument in European contract law. Though it is an accepted concept, there is no consensus regarding the role of good faith in modern civil contractual obligations. The purpose of this paper is to analyze the principle of good faith, shedding light on the concept and the description of this principle on Albanian legislation. Good faith is dealt with in its two meanings; subjective and objective, where in the objective sense of good faith is perceived as a method used to dress with moral contractual relations and to mitigate the inequalities that may result from the dogma of parties autonomy. While in the subjective view, good faith may refer to the situation in which a person acts with the confidence that he is acting in accordance with the applicable law or in a situation where a third party seeks protection. The aim of this paper is also to treat the principle of good faith under the optics of Albanian legal system. It is concluded that the doctrine in Albania is not very developed. It should be noted that there is no uniformity in jurisprudence and the debate if good faith can be excluded from the contract remains open.